Novel Biomarkers of AKI in Cirrhosis - Juanola, Adrià; Ma, Ann T.; Pose, Elisa; Ginès, Pere (Seminars in Liver Disease, 2022)
Acute kidney injury (AKI) is a frequent complication in patients with cirrhosis that is associated with poor outcomes and decreased survival. The definition of AKI in cirrhosis is currently based on changes of serum creatinine levels with respect to baseline values. Differential diagnosis of the causes of AKI is of major relevance, considering that some causes of AKI, such as hepatorenal syndrome, have specific treatment options and different prognosis. Prediction of kidney function recovery and patients' survival is also crucial in this patient population to guide clinical decisions. AKI biomarkers in cirrhosis have emerged as a promising tool for differential diagnosis and prognosis in this situation. There are consistent data showing that some urine biomarkers, particularly neutrophil gelatinase-associated lipocalin, may be useful in daily clinical practice for the differential diagnosis of the cause of AKI in cirrhosis. AKI biomarkers may constitute a useful tool for use in differential diagnosis, prognosis of renal function, and survival in patients with cirrhosis. This review focuses on the current state of knowledge and future perspective of novel biomarkers of AKI in cirrhosis.
Keywords: AKI; cirrhosis; HRS; biomarkers; novel; NGAL; IL-18; cystatin C; KIM-1